A method for making nano-SiO2-Al2O3 composite material from fly ash and applying the same to coating of lithium battery separator

CN123003187APending Publication Date: 2026-10-30SHENDONG TIANLONG GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610880038.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

本发明的目的是提出一种利用粉煤灰制作纳米SiO2-Al2O3复合材料并用于锂电池隔膜涂层的方法,解决相关技术中锂电池隔膜热稳定性差、抗穿刺性能差的问题

Benefits of technology

1)复合涂层中Al2O3的高熔点和SiO2的三维网状结构抑制基膜热收缩,提高锂电池隔膜热稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003187A_ABST
    Figure CN123003187A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium battery separator, and relates to a method for preparing nano SiO2-Al2O3 composite material from fly ash and applying the composite material to lithium battery separator coating, which comprises the following steps: 1) nano SiO2 preparation; 2) Al2O3 preparation; 3) nano SiO2-Al2O3 composite coating material preparation; and 4) lithium battery separator coating preparation.The present application has the following beneficial effects: 1) the high melting point of Al2O3 and the three-dimensional network structure of SiO2 in the composite coating inhibit the thermal shrinkage of the base film, thereby improving the thermal stability of the lithium battery separator; and 2) the nano SiO2-Al2O3 composite coating improves the puncture resistance of the lithium battery separator by 28.4%-70.7% through synergistic effect, which is much higher than that of the base film without coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery separator technology, and to a method for preparing nano-SiO2-Al2O3 composite material using fly ash and using it as a coating for lithium battery separators. Background Technology

[0002] The application of lithium batteries in electric vehicles, new energy storage, and other fields continues to expand, and the market's requirements for their performance and safety are constantly increasing. Traditional lithium battery separators have significant defects. In high-temperature environments, traditional lithium battery separators are prone to shrinkage, affecting their puncture resistance and potentially leading to battery short circuits and thermal runaway, which greatly threatens battery safety.

[0003] To address these issues, the industry commonly employs the method of adding inorganic coating components to the diaphragm, which can improve the diaphragm's thermal stability and puncture resistance to some extent. However, traditional inorganic coatings exhibit poor interfacial compatibility with commonly used polyolefin-based membranes. Under high-temperature conditions, this incompatibility leads to a significant decrease in the adhesion between the inorganic coating and the base membrane, resulting in coating peeling and ultimately limiting the improvement of the diaphragm's thermal stability and puncture resistance.

[0004] Nano-silica (SiO2) possesses a large specific surface area, good chemical stability, and high porosity, which can significantly improve the electrolyte wettability and ion conduction efficiency of the separator. Alumina (Al2O3), on the other hand, exhibits high hardness, excellent thermal stability, and mechanical strength, enhancing the separator's high-temperature resistance and puncture resistance. Combining these two materials to form a nano-SiO2-Al2O3 composite coating can achieve complementary performance, addressing the shortcomings of single coatings in terms of thermal stability, mechanical strength, or ion conduction efficiency. This has significant theoretical and engineering application value for promoting the development of high-safety, high-energy-density lithium batteries. Summary of the Invention

[0005] Purpose of the invention The purpose of this invention is to propose a method for preparing nano-SiO2-Al2O3 composite materials using fly ash and applying them as coatings for lithium battery separators, thereby solving the problems of poor thermal stability and poor puncture resistance in related technologies. Technical solution

[0006] A method for preparing nano-SiO2-Al2O3 composite material using fly ash and applying it as a coating for lithium battery separators, the specific steps of which are as follows: 1) Preparation of nano-SiO2: Fly ash, soluble alkali metal salt and water are mixed under the first microwave condition to generate a mixed product of desiliconized fly ash and sodium silicate solution. The mixed product is separated to obtain desiliconized fly ash as filter residue and sodium silicate extract as filtrate. Under the second microwave condition, acid solution is added to sodium silicate extract to adjust the pH to 7-8. The resulting mixture is centrifuged, washed and dried to obtain nano-SiO2. 2) Al2O3 preparation: Fly ash is uniformly mixed with sulfuric acid solution with a mass concentration of 70% to 98%, calcined and solidified, and granulated after natural cooling. The resulting particles are subjected to two-stage fluidized bed calcination. Hydrochloric acid solution with a mass concentration of 20% to 36% is added to the product and stirred evenly. After holding at 150 to 200°C for 1 to 2 hours, solid-liquid separation is performed to obtain aluminum chloride solution. Hydrogen chloride gas is introduced into the aluminum chloride solution at a temperature of 25 to 40°C until the solution stabilizes and no more crystalline aluminum chloride is produced. Then, the crystalline aluminum chloride is calcined in two stages to obtain Al2O3. 3) Preparation of nano-SiO2-Al2O3 composite coating material: The nano-SiO2 obtained in step 1), the Al2O3 obtained in step 2), and hexagonal boron nitride are mixed, sintered, and naturally cooled to obtain a mixed solid material. The dispersant and water are mixed and added to the mixed solid material, and stirred to prepare a composite material mixed solution. The binder and thickener are added to the composite material mixed solution, stirred evenly, and then sand-milled to obtain the nano-SiO2-Al2O3 composite coating material. 4) Preparation of lithium battery separator coating: The obtained coating material is coated on the base fabric and dried to obtain a nano-SiO2-Al2O3 coated lithium battery separator.

[0007] Furthermore, in step 1), the fly ash is fly ash obtained by grinding with a planetary ball mill, and the particle size of the fly ash is less than 10 μm; the soluble metal salt is sodium hydroxide or potassium hydroxide; the acid solution is one of citric acid, hydrochloric acid or oxalic acid; the mass ratio of fly ash to soluble metal salt is 1:(0.5-2), and the mass ratio of the sum of fly ash and soluble metal salt to water is 1:(1-4).

[0008] Furthermore, in step 1), the first microwave conditions are: power 550–750W, time 0.5–1.5h, and temperature 80–100℃; the second microwave conditions are: power 350–550W, time 5–25min, and temperature 60–80℃. The first and second microwaves were performed using the XH-800SP multifunctional microwave hydrothermal parallel synthesizer manufactured by Beijing Xianghu Technology Development Co., Ltd.

[0009] Furthermore, in step 2), the calcination and curing temperature is 300-350℃, the calcination and curing time is 15-30 minutes, and after natural cooling, the particles are extruded and granulated at a pressure of 80-120 MPa to obtain particles with a particle size of 1-10 mm.

[0010] Furthermore, in step 2), the two-stage fluidized bed roasting consists of two stages: low-temperature drying and high-temperature activation. The temperature of the low-temperature drying stage is 100-200°C and the time is 20-60 min. The temperature of the high-temperature activation stage is 300-400°C and the time is 20-60 min. The heating rate from the low-temperature drying stage to the high-temperature activation stage is 5-10°C / min. The reaction is carried out in a fluidized bed roasting furnace.

[0011] Furthermore, in step 2), the two-stage roasting of crystalline aluminum chloride consists of a first stage temperature and a second stage temperature. The first stage temperature is 300-350°C and the time is 60-90 min. The second stage temperature is 800-950°C and the time is 2-3 h. The heating rate from the first stage temperature to the second stage temperature is 5-15°C / min. The reaction is carried out in a box-type muffle furnace.

[0012] Furthermore, in step 3), the weight ratio of nano-SiO2, Al2O3 and hexagonal boron nitride is (5-10):(20-30):(1~5); The mixing was performed using ball milling. Yttrium-stabilized zirconia ceramic balls were used as the milling media, employing a multi-grade distribution of Φ10mm, Φ6mm, and Φ3mm balls. The mass ratio of Φ10mm, Φ6mm, and Φ3mm balls was (2.5-3.5):(3.8-4.2):(2.5-3.5). The total filling volume of the milling balls was 50%–60% of the milling jar volume. The mass ratio of the milling balls to the total mass of nano-SiO2, Al2O3, and hexagonal boron nitride was 3:1–4:1. The ball mill speed was 200–600 rpm, and the milling time was 10–20 min. The milled material D 10 The range is 0.20~0.45μm, D 50 The range is 0.65~1.50μm, D 90 The thickness is 2.30~3.10 μm; the D 10 D 50 and D 90 These represent the characteristic particle sizes corresponding to when the cumulative particle size distribution of the powder volume reaches 10%, 50%, and 90%, respectively; where D 50 D represents the median particle size, characterizing the average particle size of the powder. 10 D reflects the fine end particle size level of powder. 90 Reflects the upper limit of the coarse end particle size of the powder; Sintering is carried out under inert gas protection, with the temperature increased from room temperature to 1000-1500℃ at a heating rate of 10-15℃ / min, and then held at that temperature for 1-2 hours. The particle size of the nano-SiO2-Al2O3 composite coating material obtained by sand milling is: D 50 The diameter is 0.45~0.80μm, D 90 The thickness ranges from 1.35 to 1.80 μm.

[0013] Furthermore, in step 3), the total weight parts of nano-SiO2, Al2O3 and hexagonal boron nitride are 25-35 parts, the weight parts of dispersant are 0.2-0.5 parts, the weight parts of water are 40-50 parts, the weight parts of binder are 5-10 parts, and the weight parts of thickener are 5-10 parts.

[0014] Furthermore, in step 3), the dispersant is one or more of ammonium polyacrylate, sodium dodecylbenzene sulfate, or sodium lauryl ether sulfate; the binder is one or more of polyvinylidene fluoride or polyvinyl alcohol; and the thickener is one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, or hydroxyethyl cellulose.

[0015] Furthermore, in step 4), the coating method is single-sided coating or double-sided coating. The thickness of single-sided coating is 3~4μm, and the thickness of both sides of double-sided coating is 3~4μm. The drying temperature is 40~70℃ and the time is 5~10min.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1) The high melting point of Al2O3 and the three-dimensional network structure of SiO2 in the composite coating inhibit the thermal shrinkage of the base film and improve the thermal stability of the lithium battery separator.

[0017] 2) The nano-SiO2-Al2O3 composite coating improves the puncture resistance of lithium battery separators by 28.4%-70.7% through synergistic effect, far exceeding that of single-material coatings. Attached Figure Description

[0018] Figure 1 The XRD pattern of the nano-SiO2-Al2O3 composite material in Example 3 is shown below. Figure 2 The microstructure of the nano-SiO2-Al2O3 composite material in Example 3 is shown. Detailed Implementation

[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the specific embodiments used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the specific embodiments described below are some embodiments of the present invention. For those skilled in the art, other specific embodiments can be obtained based on these specific embodiments without creative effort.

[0021] The components of the embodiments of the invention described and shown in the specific embodiments herein can be arranged and designed in countless different configurations. Therefore, the following detailed description of the embodiments of the invention provided in the specific embodiments is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention.

[0022] In the following examples and comparative examples, the dispersant was ammonium polyacrylate, CAS number 9003-03-6, manufactured by Shandong Taihe Technology Co., Ltd. The binder was polyvinyl alcohol, PVA 22-99H, manufactured by Guangxi Wanwei Biomass Technology Co., Ltd. The thickener was carboxymethyl cellulose with a viscosity of 1500 mPa·s, manufactured by Shandong Weihong Economic and Trade Co., Ltd.

[0023] A method for preparing nano-SiO2-Al2O3 composite material using fly ash and applying it as a coating for lithium battery separators, the specific steps of which are as follows: 1) Preparation of nano-SiO2: Fly ash, soluble alkali metal salt and water are mixed under the first microwave condition to generate a mixed product of desiliconized fly ash and sodium silicate solution. The mixed product is separated to obtain desiliconized fly ash as filter residue and sodium silicate extract as filtrate. Under the second microwave condition, acid solution is added to sodium silicate extract to adjust the pH to 7-8. The resulting mixture is centrifuged, washed and dried to obtain nano-SiO2. The fly ash is obtained by grinding with a planetary ball mill, and the particle size of the fly ash is less than 10 μm; the soluble metal salt is sodium hydroxide or potassium hydroxide; the acid solution is one of citric acid, hydrochloric acid or oxalic acid; the mass ratio of fly ash to soluble metal salt is 1:(0.5~2), and the mass ratio of the sum of fly ash and soluble metal salt to water is 1:(1~4); The first microwave conditions were: power 550–750W, time 0.5–1.5h, and temperature 80–100℃; the second microwave conditions were: power 350–550W, time 5–25min, and temperature 60–80℃. The first and second microwave conditions were achieved using the XH-800SP multifunctional microwave hydrothermal parallel synthesizer manufactured by Beijing Xianghu Technology Development Co., Ltd.

[0024] 2) Al2O3 preparation: Fly ash is uniformly mixed with sulfuric acid solution with a mass concentration of 70% to 98%, calcined and solidified, and granulated after natural cooling. The resulting particles are subjected to two-stage fluidized bed calcination. Hydrochloric acid solution with a mass concentration of 20% to 36% is added to the product and stirred evenly. After holding at 150 to 200°C for 1 to 2 hours, solid-liquid separation is performed to obtain aluminum chloride solution. Hydrogen chloride gas is introduced into the aluminum chloride solution at a temperature of 25 to 40°C until the solution stabilizes and no more crystalline aluminum chloride is produced. Then, the crystalline aluminum chloride is calcined in two stages to obtain Al2O3. The calcination and curing temperature is 300-350℃, and the calcination and curing time is 15-30 minutes. After natural cooling, the particles are extruded and granulated at a pressure of 80-120 MPa to obtain particles with a particle size of 1-10 mm. The two-stage fluidized bed roasting consists of two stages: low-temperature drying and high-temperature activation. The temperature of the low-temperature drying stage is 100-200℃ and the time is 20-60 min. The temperature of the high-temperature activation stage is 300-400℃ and the time is 20-60 min. The heating rate from the low-temperature drying stage to the high-temperature activation stage is 5-10°C / min. The reaction is carried out in a fluidized bed roasting furnace. The two-stage calcination of crystalline aluminum chloride consists of a first stage temperature and a second stage temperature. The first stage temperature is 300-350℃ and the time is 60-90 min. The second stage temperature is 800-950℃ and the time is 2-3 h. The heating rate from the first stage temperature to the second stage temperature is 5-15°C / min. The reaction is carried out in a box-type muffle furnace.

[0025] 3) Preparation of nano-SiO2-Al2O3 composite coating material: The nano-SiO2 obtained in step 1), the Al2O3 obtained in step 2), and hexagonal boron nitride are mixed, sintered, and naturally cooled to obtain a mixed solid material. The dispersant and water are mixed and added to the mixed solid material, and stirred to prepare a composite material mixed solution. The binder and thickener are added to the composite material mixed solution, stirred evenly, and then sand-milled to obtain the nano-SiO2-Al2O3 composite coating material. The weight ratio of nano-SiO2, Al2O3, and hexagonal boron nitride is (5-10):(20-30):(1~5); the mixture is ball-milled, using yttrium-stabilized zirconia ceramic balls as the milling media. Multi-grade milling balls with diameters of Φ10mm, Φ6mm, and Φ3mm are used, with a mass ratio of Φ10mm, Φ6mm, and Φ3mm milling balls of (2.5-3.5):(3.8-4.2):(2.5-3.5). The total filling volume of the milling balls is 50%–60% of the milling jar volume. The mass ratio of the milling balls to the total mass of nano-SiO2, Al2O3, and hexagonal boron nitride is 3:1–4:1. The mill speed is 200–600 rpm, and the milling time is 10–20 min. The material after milling is D. 10The range is 0.20~0.45μm, D 50 The range is 0.65~1.50μm, D 90 The thickness is 2.30~3.10 μm; the D 10 D 50 and D 90 These represent the characteristic particle sizes corresponding to when the cumulative particle size distribution of the powder volume reaches 10%, 50%, and 90%, respectively; where D 50 D represents the median particle size, characterizing the average particle size of the powder. 10 D reflects the fine end particle size level of powder. 90 Reflects the upper limit of the coarse end particle size of the powder; Sintering is carried out under the protection of an inert gas (one of helium, argon or neon), with the temperature increased from room temperature to 1000-1500℃ at a heating rate of 10-15℃ / min, and then held at that temperature for 1-2 hours. The particle size of the nano-SiO2-Al2O3 composite coating material obtained by sand milling is: D 50 The diameter is 0.45~0.80μm, D 90 Its thickness is 1.35~1.80 μm; The total weight of nano-SiO2, Al2O3 and hexagonal boron nitride is 25-35 parts, the weight of dispersant is 0.2-0.5 parts, the weight of water is 40-50 parts, the weight of binder is 5-10 parts, and the weight of thickener is 5-10 parts. The dispersant is one or more of ammonium polyacrylate, sodium dodecylbenzene sulfate, or sodium lauryl ether sulfate; the binder is one or more of polyvinylidene fluoride or polyvinyl alcohol; and the thickener is one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, or hydroxyethyl cellulose.

[0026] 4) Preparation of lithium battery separator coating: The obtained coating material is coated on the base fabric and dried to obtain a nano-SiO2-Al2O3 coated lithium battery separator; The coating method is single-sided coating or double-sided coating. The thickness of single-sided coating is 3~4μm, and the thickness of both sides of double-sided coating is 3~4μm. The drying temperature is 40~70℃ and the time is 5~10min.

[0027] Example 1

[0028] A method for preparing nano-SiO2-Al2O3 composite material using fly ash and applying it as a coating for lithium battery separators, the specific steps of which are as follows: 1) Preparation of nano-SiO2: Fly ash, soluble alkali metal salt and water are mixed under the first microwave condition to generate a mixed product of desiliconized fly ash and sodium silicate solution. The mixed product is separated to obtain desiliconized fly ash as filter residue and sodium silicate extract as filtrate. Under the second microwave condition, acid solution is added to sodium silicate extract to adjust the pH to 7. The resulting mixture is centrifuged, washed and dried to obtain nano-SiO2. The fly ash is obtained by grinding in a planetary ball mill. The particle size of the fly ash is screened to be less than 10μm. The soluble metal salt is sodium hydroxide. The acid solution is citric acid. The mass ratio of fly ash to soluble metal salt is 1:0.5, and the mass ratio of the sum of fly ash and soluble metal salt to water is 1:1. The first microwave conditions were: power 550W, time 1.5h, and temperature 80℃; the second microwave conditions were: power 350W, time 25min, and temperature 60℃. The first and second microwave conditions were performed using the XH-800SP multifunctional microwave hydrothermal parallel synthesizer manufactured by Beijing Xianghu Technology Development Co., Ltd.

[0029] 2) Al2O3 preparation: fly ash was uniformly mixed with a 70% sulfuric acid solution, calcined and solidified, and granulated after natural cooling. The resulting particles were subjected to two-stage fluidized bed calcination. A 36% hydrochloric acid solution was added to the product and stirred evenly. After holding at 150℃ for 2 hours, solid-liquid separation was performed to obtain an aluminum chloride solution. Hydrogen chloride gas was introduced into the aluminum chloride solution at a solution temperature of 25℃ until the solution stabilized and no more crystalline aluminum chloride was produced. The crystalline aluminum chloride was then calcined in two stages to obtain Al2O3. The calcination and curing temperature is 300℃, and the calcination and curing time is 30 minutes. After natural cooling, the particles are extruded and granulated at a pressure of 120MPa to obtain particles with a particle size of 1-10mm. The two-stage fluidized bed roasting consists of two stages: low-temperature drying and high-temperature activation. The low-temperature drying stage is at 100°C for 60 minutes, and the high-temperature activation stage is at 300°C for 60 minutes. The heating rate from the low-temperature drying stage to the high-temperature activation stage is 5°C / min. The reaction is carried out in a fluidized bed roasting furnace. The two-stage calcination of crystalline aluminum chloride consists of a first stage temperature and a second stage temperature. The first stage temperature is 300℃ for 90 min, and the second stage temperature is 800℃ for 3 h. The heating rate from the first stage temperature to the second stage temperature is 5°C / min, and the reaction is carried out in a box-type muffle furnace.

[0030] 3) Preparation of nano-SiO2-Al2O3 composite coating material: The nano-SiO2 obtained in step 1), the Al2O3 obtained in step 2), and hexagonal boron nitride are mixed, sintered, and naturally cooled to obtain a mixed solid material. The dispersant and water are mixed and added to the mixed solid material, and stirred to prepare a composite material mixed solution. The binder and thickener are added to the composite material mixed solution, stirred evenly, and then sand-milled to obtain the nano-SiO2-Al2O3 composite coating material. The weight ratio of nano-SiO2, Al2O3, and hexagonal boron nitride was 5:20:1. The mixture was ball-milled using yttrium-stabilized zirconia ceramic balls of Φ10mm, Φ6mm, and Φ3mm. The mass ratio of Φ10mm, Φ6mm, and Φ3mm balls was 2.5:3.8:2.5. The total filling volume of the grinding balls was 50% of the grinding jar volume. The mass ratio of the grinding balls to the total mass of nano-SiO2, Al2O3, and hexagonal boron nitride was 3:1. The ball mill speed was 200 rpm, and the milling time was 20 min. The resulting material D... 10 It is 0.20μm, D 50 For 0.65μm, D 90 It is 2.30 μm; the D 10 D 50 and D 90 These represent the characteristic particle sizes corresponding to when the cumulative particle size distribution of the powder volume reaches 10%, 50%, and 90%, respectively; where D 50 D represents the median particle size, characterizing the average particle size of the powder. 10 D reflects the fine end particle size level of powder. 90 Reflects the upper limit of the coarse end particle size of the powder; Sintering is carried out under helium protection by heating from room temperature to 1000℃ at a heating rate of 10℃ / min and holding at that temperature for 2 hours. The particle size of the nano-SiO2-Al2O3 composite coating material obtained by sand milling is: D 50 It is 0.45μm, D 90 It is 1.35μm; The total weight of nano-SiO2, Al2O3 and hexagonal boron nitride is 25 parts, the weight of dispersant is 0.2 parts, the weight of water is 40 parts, the weight of binder is 5 parts, and the weight of thickener is 5 parts. The dispersant is ammonium polyacrylate; the binder is polyvinylidene fluoride; and the thickener is carboxymethyl cellulose.

[0031] 4) Preparation of lithium battery separator coating: The obtained coating material is coated on the base fabric and dried to obtain a nano-SiO2-Al2O3 coated lithium battery separator; The coating method is single-sided coating, the thickness of the single-sided coating is 3μm, the drying temperature is 40℃, and the time is 10min.

[0032] Example 2

[0033] A method for preparing nano-SiO2-Al2O3 composite material using fly ash and applying it as a coating for lithium battery separators, the specific steps of which are as follows: 1) Preparation of nano-SiO2: Fly ash, soluble alkali metal salt and water are mixed under the first microwave condition to generate a mixed product of desiliconized fly ash and sodium silicate solution. The mixed product is separated to obtain desiliconized fly ash as filter residue and sodium silicate extract as filtrate. Under the second microwave condition, acid solution is added to sodium silicate extract to adjust the pH to 8. The resulting mixture is centrifuged, washed and dried to obtain nano-SiO2. The fly ash is obtained by grinding in a planetary ball mill. The particle size of the fly ash is screened to be less than 10μm. The soluble metal salt is potassium hydroxide. The acid solution is hydrochloric acid. The mass ratio of fly ash to soluble metal salt is 1:2, and the mass ratio of the sum of fly ash and soluble metal salt to water is 1:4. The first microwave conditions were: power 750W, time 0.5h, and temperature 100℃; the second microwave conditions were: power 550W, time 5min, and temperature 80℃. The first and second microwave conditions were performed using the XH-800SP multifunctional microwave hydrothermal parallel synthesizer manufactured by Beijing Xianghu Technology Development Co., Ltd.

[0034] 2) Al2O3 preparation: fly ash was uniformly mixed with 98% sulfuric acid solution, calcined and solidified, and granulated after natural cooling. The resulting particles were subjected to two-stage fluidized bed calcination. A 20% hydrochloric acid solution was added to the product and stirred evenly. After holding at 200℃ for 1 hour, solid-liquid separation was performed to obtain aluminum chloride solution. Hydrogen chloride gas was introduced into the aluminum chloride solution at 40℃ until the solution temperature stabilized and no more crystalline aluminum chloride was produced. Then, the crystalline aluminum chloride was calcined in two stages to obtain Al2O3. The calcination and curing temperature was 350℃, and the calcination and curing time was 15 minutes. After natural cooling, the particles were extruded and granulated at a pressure of 80 MPa to obtain particles with a particle size of 1 to 10 mm. The two-stage fluidized bed roasting consists of two stages: low-temperature drying and high-temperature activation. The low-temperature drying stage is at 200°C for 20 minutes, and the high-temperature activation stage is at 400°C for 20 minutes. The heating rate from the low-temperature drying stage to the high-temperature activation stage is 10°C / min, and the reaction is carried out in a fluidized bed roasting furnace. The two-stage calcination of crystalline aluminum chloride consists of a first stage temperature and a second stage temperature. The first stage temperature is 350℃ for 60 min, and the second stage temperature is 950℃ for 2 h. The heating rate from the first stage temperature to the second stage temperature is 15°C / min, and the reaction is carried out in a box-type muffle furnace.

[0035] 3) Preparation of nano-SiO2-Al2O3 composite coating material: The nano-SiO2 obtained in step 1), the Al2O3 obtained in step 2), and hexagonal boron nitride are mixed, sintered, and naturally cooled to obtain a mixed solid material. The dispersant and water are mixed and added to the mixed solid material, and stirred to prepare a composite material mixed solution. The binder and thickener are added to the composite material mixed solution, stirred evenly, and then sand-milled to obtain the nano-SiO2-Al2O3 composite coating material. The weight ratio of nano-SiO2, Al2O3, and hexagonal boron nitride was 2:6:1. The mixture was ball-milled using yttrium-stabilized zirconia ceramic balls as the milling media. A multi-grade milling ball with diameters of Φ10mm, Φ6mm, and Φ3mm was used, with a mass ratio of Φ10mm, Φ6mm, and Φ3mm balls of 5:6:5. The total filling volume of the milling balls was 60% of the milling jar volume. The mass ratio of the milling balls to the total mass of nano-SiO2, Al2O3, and hexagonal boron nitride was 4:1. The mill speed was 600 rpm, and the milling time was 10 minutes. The resulting material D... 10 It is 0.45μm, D 50 It is 1.50 μm, D 90 It is 3.10 μm; the D 10 D 50 and D 90 These represent the characteristic particle sizes corresponding to when the cumulative particle size distribution of the powder volume reaches 10%, 50%, and 90%, respectively; where D 50 D represents the median particle size, characterizing the average particle size of the powder. 10 D reflects the fine end particle size level of powder. 90 Reflects the upper limit of the coarse end particle size of the powder; Sintering was carried out under argon protection, with the temperature increased from room temperature to 1500℃ at a rate of 15℃ / min, and then held at that temperature for 1 hour. The particle size of the nano-SiO2-Al2O3 composite coating material obtained by sand milling is: D 50 It is 0.80μm, D 90 It is 1.80 μm; The total weight of nano-SiO2, Al2O3 and hexagonal boron nitride is 35 parts, the weight of dispersant is 0.5 parts, the weight of water is 50 parts, the weight of binder is 10 parts, and the weight of thickener is 10 parts. The dispersant is ammonium polyacrylate and sodium dodecylbenzene sulfate; the binder is polyvinyl alcohol; and the thickener is carboxymethyl cellulose and sodium carboxymethyl cellulose.

[0036] 4) Preparation of lithium battery separator coating: The obtained coating material is coated on the base fabric and dried to obtain a nano-SiO2-Al2O3 coated lithium battery separator; The coating method is double-sided coating, with the thicknesses of the two sides being 3μm and 4μm respectively. The drying temperature is 70℃ and the drying time is 5min.

[0037] Example 3

[0038] A method for preparing nano-SiO2-Al2O3 composite material using fly ash and applying it as a coating for lithium battery separators, the specific steps of which are as follows: 1) Preparation of nano-SiO2: Fly ash, soluble alkali metal salt and water are mixed under the first microwave condition to generate a mixed product of desiliconized fly ash and sodium silicate solution. The mixed product is separated to obtain desiliconized fly ash as filter residue and sodium silicate extract as filtrate. Under the second microwave condition, acid solution is added to sodium silicate extract to adjust the pH to 7.5. The resulting mixture is centrifuged, washed and dried to obtain nano-SiO2. The fly ash is obtained by grinding in a planetary ball mill. The particle size of the fly ash is screened to be less than 10μm. The soluble metal salt is sodium hydroxide. The acid solution is oxalic acid. The mass ratio of fly ash to soluble metal salt is 1:1, and the mass ratio of the sum of fly ash and soluble metal salt to water is 1:2. The first microwave conditions were: power 650W, time 1 hour, and temperature 90℃; the second microwave conditions were: power 450W, time 15 minutes, and temperature 70℃. The first and second microwave conditions were performed using the XH-800SP multifunctional microwave hydrothermal parallel synthesizer manufactured by Beijing Xianghu Technology Development Co., Ltd.

[0039] 2) Al2O3 preparation: Fly ash was uniformly mixed with 84% sulfuric acid solution, calcined and solidified, and granulated after natural cooling. The resulting particles were subjected to two-stage fluidized bed calcination. A 28% hydrochloric acid solution was added to the product and stirred evenly. After holding at 175℃ for 1.5h, solid-liquid separation was performed to obtain aluminum chloride solution. Hydrogen chloride gas was introduced into the aluminum chloride solution at 33℃ until the solution temperature stabilized and no more crystalline aluminum chloride was produced. Then, the crystalline aluminum chloride was calcined in two stages to obtain Al2O3. The calcination and curing temperature was 325℃, and the calcination and curing time was 24 minutes. After natural cooling, the particles were extruded and granulated at a pressure of 100 MPa to obtain particles with a particle size of 1 to 10 mm. The two-stage fluidized bed roasting consists of two stages: low-temperature drying and high-temperature activation. The low-temperature drying stage is at 150°C for 40 minutes, and the high-temperature activation stage is at 350°C for 40 minutes. The heating rate from the low-temperature drying stage to the high-temperature activation stage is 7°C / min. The reaction is carried out in a fluidized bed roasting furnace. The two-stage calcination of crystalline aluminum chloride consists of a first stage temperature and a second stage temperature. The first stage temperature is 325℃ and the time is 75 min, while the second stage temperature is 880℃ and the time is 2.5 h. The heating rate from the first stage temperature to the second stage temperature is 10°C / min, and the reaction is carried out in a box-type muffle furnace.

[0040] 3) Preparation of nano-SiO2-Al2O3 composite coating material: The nano-SiO2 obtained in step 1), the Al2O3 obtained in step 2), and hexagonal boron nitride are mixed, sintered, and naturally cooled to obtain a mixed solid material. The dispersant and water are mixed and added to the mixed solid material, and stirred to prepare a composite material mixed solution. The binder and thickener are added to the composite material mixed solution, stirred evenly, and then sand-milled to obtain the nano-SiO2-Al2O3 composite coating material. The weight ratio of nano-SiO2, Al2O3, and hexagonal boron nitride was 7:25:3. The mixture was ball-milled using yttrium-stabilized zirconia ceramic balls of Ф10mm, Ф6mm, and Ф3mm diameters as the milling media. The mass ratio of Ф10mm, Ф6mm, and Ф3mm balls was 3:4:3, and the total filling volume of the milling balls was 55% of the milling jar volume. The mass ratio of the milling balls to the total mass of nano-SiO2, Al2O3, and hexagonal boron nitride was 3.5:1. The mill speed was 400 rpm, and the milling time was 15 minutes. The resulting material D... 10 0.30μm, D 50 1.00 μm, D 90 It is 2.80 μm; the D 10 D 50 and D 90 These represent the characteristic particle sizes corresponding to when the cumulative particle size distribution of the powder volume reaches 10%, 50%, and 90%, respectively; where D 50 D represents the median particle size, characterizing the average particle size of the powder. 10 D reflects the fine end particle size level of powder. 90 Reflects the upper limit of the coarse end particle size of the powder; Sintering was carried out under neon protection, with the temperature increased from room temperature to 1250℃ at a rate of 12℃ / min, and then held at that temperature for 1.5h. The particle size of the nano-SiO2-Al2O3 composite coating material obtained by sand milling is: D 50 It is 0.60μm, D 90 It is 1.50 μm; The total weight of nano-SiO2, Al2O3 and hexagonal boron nitride is 30 parts, the weight of dispersant is 0.3 parts, the weight of water is 45 parts, the weight of binder is 7 parts, and the weight of thickener is 7 parts. The dispersants are ammonium polyacrylate, sodium dodecylbenzene sulfate, and sodium lauryl alcohol polyoxyethylene ether sulfate; the binders are polyvinylidene fluoride and polyvinyl alcohol; and the thickeners are carboxymethyl cellulose, sodium carboxymethyl cellulose, and hydroxyethyl cellulose.

[0041] 4) Preparation of lithium battery separator coating: The obtained coating material is coated on the base fabric and dried to obtain a nano-SiO2-Al2O3 coated lithium battery separator; The coating method is double-sided coating, with a thickness of 4μm on both sides. The drying temperature is 55℃ and the drying time is 7min.

[0042] Comparative Example 1 The only difference between this comparative example and Example 2 is that in this comparative example, nano-silica is replaced with micron-silica.

[0043] Comparative Example 2 The only difference between this comparative example and Example 2 is that in this comparative example, hexagonal boron nitride is replaced with an equal amount of cubic boron nitride.

[0044] The transverse (TD) and longitudinal (MD) heat shrinkage rates and puncture strengths of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1 below: Table 1. Thermal stability test results of Examples 1-3 and Comparative Examples 1-2

[0045] As shown in Table 1, the puncture strength of the nano-SiO2-Al2O3 coated lithium battery separator can reach 10.4-12.8 N, which is 28.4%-70.7% higher than that of the uncoated base film. The thermal shrinkage rate of the separators in Examples 1-3 is significantly reduced and the puncture strength is significantly improved, indicating that nano-silica, alumina and boron nitride in the nano-SiO2-Al2O3 coated lithium battery separator have a synergistic effect, which can significantly improve the thermal stability and puncture resistance of the lithium battery separator.

[0046] Figure 1 The XRD pattern of the nano-SiO2-Al2O3 composite material in Example 3 is shown below; Figure 1It can be seen that the nano-SiO2-Al2O3 composite material exhibits characteristic diffraction peaks of sillimanite and mullite, indicating that nano-SiO2 and Al2O3 react to form thermally stable sillimanite and mullite crystalline phases. When this composite material is used in lithium battery separators, the high-melting-point mullite and sillimanite phases can significantly improve the thermal stability of the separator and reduce thermal shrinkage. The Al-Si oxide phase has good electrolyte compatibility and electrochemical stability, which can improve the separator's liquid retention capacity and ionic conductivity. At the same time, sillimanite and mullite are rigid crystalline phases that can enhance the separator's puncture resistance, thereby improving the cycle stability and safety of lithium batteries.

[0047] Figure 2 The microstructure of the nano-SiO2-Al2O3 composite material in Example 3 is shown. This nano-SiO2-Al2O3 composite material exhibits an overall aggregated and stacked particle structure, with particle sizes mainly distributed in the micrometer range. It consists of a large number of closely aggregated near-polygonal grains with clear grain boundaries and complete crystallization, corresponding to the rigid crystalline phases of mullite and sillimanite in XRD. The dense grain structure can construct a rigid framework. Simultaneously, the high-hardness, high-melting-point Al2O3 particles interlock to form a rigid framework, while SiO2 fills the spaces within a continuous three-dimensional network structure. The synergistic effect of these two elements not only effectively suppresses the thermal shrinkage of the base film at high temperatures and improves the thermal stability of the separator, but also constructs a protective system that combines rigid support and elastic buffering, further enhancing the mechanical strength and electrolyte affinity of the coating, providing a reliable guarantee for the safe and stable operation of the lithium battery. Furthermore, the presence of interconnected micropores between the particles facilitates electrolyte wetting and retention. The composite material exhibits good overall morphological uniformity and lacks excessively large agglomerates. This microstructure can effectively improve the mechanical stability and heat shrinkage resistance of the lithium battery separator coating.

[0048] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all embodiments here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing nano-SiO2-Al2O3 composite materials using fly ash and applying them as coatings for lithium battery separators, characterized in that: The specific steps are as follows: 1) Preparation of nano-SiO2: Fly ash, soluble alkali metal salt and water are mixed under the first microwave condition to generate a mixed product of desiliconized fly ash and sodium silicate solution. The mixed product is separated to obtain desiliconized fly ash as filter residue and sodium silicate extract as filtrate. Under the second microwave condition, acid solution was added to the sodium silicate extract to adjust the pH to 7-8. The resulting mixture was centrifuged, washed and dried to obtain nano-SiO2. 2) Al2O3 preparation: Fly ash is uniformly mixed with sulfuric acid solution with a mass concentration of 70% to 98%, calcined and solidified, and granulated after natural cooling. The resulting particles are subjected to two-stage fluidized bed calcination. Hydrochloric acid solution with a mass concentration of 20% to 36% is added to the product and stirred evenly. After holding at 150 to 200°C for 1 to 2 hours, solid-liquid separation is performed to obtain aluminum chloride solution. Hydrogen chloride gas is introduced into the aluminum chloride solution at a temperature of 25 to 40°C until the solution stabilizes and no more crystalline aluminum chloride is produced. Then, the crystalline aluminum chloride is calcined in two stages to obtain Al2O3. 3) Preparation of nano-SiO2-Al2O3 composite coating material: The nano-SiO2 obtained in step 1), the Al2O3 obtained in step 2), and hexagonal boron nitride are mixed, sintered, and naturally cooled to obtain a mixed solid material. The dispersant and water are mixed and added to the mixed solid material, and stirred to prepare a composite material mixed solution. The binder and thickener are added to the composite material mixed solution, stirred evenly, and then sand-milled to obtain the nano-SiO2-Al2O3 composite coating material. 4) Preparation of lithium battery separator coating: The obtained coating material is coated on the base fabric and dried to obtain a nano-SiO2-Al2O3 coated lithium battery separator.

2. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 1 and using it for lithium battery separator coating, characterized in that: In step 1), the fly ash is obtained by grinding with a planetary ball mill, and the particle size of the fly ash is less than 10 μm; the soluble metal salt is sodium hydroxide or potassium hydroxide; the acid solution is one of citric acid, hydrochloric acid or oxalic acid; the mass ratio of fly ash to soluble metal salt is 1:(0.5-2), and the mass ratio of the sum of fly ash and soluble metal salt to water is 1:(1-4).

3. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 1 and using it for lithium battery separator coating, characterized in that: In step 1), the first microwave conditions are: power 550–750W, time 0.5–1.5h, and temperature 80–100℃; the second microwave conditions are: power 350–550W, time 5–25min, and temperature 60–80℃. The first and second microwave conditions were performed using the XH-800SP multifunctional microwave hydrothermal parallel synthesizer manufactured by Beijing Xianghu Technology Development Co., Ltd.

4. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 1 and using it for lithium battery separator coating, characterized in that: In step 2), the calcination and curing temperature is 300-350℃, the calcination and curing time is 15-30 minutes, and after natural cooling, the particles are extruded and granulated at a pressure of 80-120 MPa to obtain particles with a particle size of 1-10 mm.

5. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 1 and using it for lithium battery separator coating, characterized in that: In step 2), the two-stage fluidized bed roasting consists of two stages: low-temperature drying and high-temperature activation. The temperature of the low-temperature drying stage is 100-200°C and the time is 20-60 min. The temperature of the high-temperature activation stage is 300-400°C and the time is 20-60 min. The heating rate from the low-temperature drying stage to the high-temperature activation stage is 5-10°C / min. The reaction is carried out in a fluidized bed roasting furnace.

6. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 1 and using it for lithium battery separator coating, characterized in that: In step 2), the two-stage roasting of crystalline aluminum chloride consists of a first stage temperature and a second stage temperature. The first stage temperature is 300-350°C and the time is 60-90 min. The second stage temperature is 800-950°C and the time is 2-3 h. The heating rate from the first stage temperature to the second stage temperature is 5-15°C / min. The reaction is carried out in a box-type muffle furnace.

7. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 1 and using it for lithium battery separator coating, characterized in that: In step 3), the weight ratio of nano-SiO2, Al2O3 and hexagonal boron nitride is (5-10):(20-30):(1~5); The mixing was performed using ball milling. Yttrium-stabilized zirconia ceramic balls were used as the milling media, employing a multi-grade distribution of Φ10mm, Φ6mm, and Φ3mm balls. The mass ratio of Φ10mm, Φ6mm, and Φ3mm balls was (2.5-3.5):(3.8-4.2):(2.5-3.5). The total filling volume of the milling balls was 50%–60% of the milling jar volume. The mass ratio of the milling balls to the total mass of nano-SiO2, Al2O3, and hexagonal boron nitride was 3:1–4:

1. The ball mill speed was 200–600 rpm, and the milling time was 10–20 min. The milled material D 10 The range is 0.20~0.45μm, D 50 The range is 0.65~1.50μm, D 90 The thickness is 2.30~3.10 μm; the D 10 D 50 and D 90 These represent the characteristic particle sizes corresponding to when the cumulative particle size distribution of the powder volume reaches 10%, 50%, and 90%, respectively; where D 50 D represents the median particle size, characterizing the average particle size of the powder. 10 D reflects the fine end particle size level of powder. 90 Reflects the upper limit of the coarse end particle size of the powder; Sintering is carried out under inert gas protection, with the temperature increased from room temperature to 1000-1500℃ at a heating rate of 10-15℃ / min, and then held at that temperature for 1-2 hours. The particle size of the nano-SiO2-Al2O3 composite coating material obtained by sand milling is: D 50 The diameter is 0.45~0.80μm, D 90 The thickness ranges from 1.35 to 1.80 μm.

8. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 7 and using it for lithium battery separator coating, characterized in that: In step 3), the total weight of nano-SiO2, Al2O3 and hexagonal boron nitride is 25-35 parts, the weight of dispersant is 0.2-0.5 parts, the weight of water is 40-50 parts, the weight of binder is 5-10 parts, and the weight of thickener is 5-10 parts.

9. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 1 or 8 and using it for lithium battery separator coating, characterized in that: The dispersant in step 3) is one or more of ammonium polyacrylate, sodium dodecylbenzene sulfate, or sodium lauryl ether sulfate; the binder is one or more of polyvinylidene fluoride or polyvinyl alcohol; and the thickener is one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, or hydroxyethyl cellulose.

10. The method for preparing nano-SiO2-Al2O3 composite material using fly ash according to claim 1 and using it for lithium battery separator coating, characterized in that: In step 4), the coating method is single-sided coating or double-sided coating. The thickness of single-sided coating is 3~4μm, and the thickness of both sides of double-sided coating is 3~4μm. The drying temperature is 40~70℃ and the time is 5~10min.